Optimalisasi Keuntungan Penjualan Kopi Tubruk Menggunakan Pemrograman Linier Melalui Metode Simpleks: Studi Kasus Umkm Pada Photongopi Bang Marko - Munandar, Zikri Bagas; Haludin, Guntur; Albari, Pascal Kharua; Dhiya’ulhaq, Mufadhal Daffa; adha, Muhamad akmal; Mundzir, Ahmad (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to optimize the profit of Tubruk coffee sales in Kopi Bang Marko, a small and medium-sized enterprise (SME) in Tangerang Selatan, Indonesia, using linear programming through the simplex method. The research utilizes a combination of observation and interviews to gather data on raw material availability, coffee sales, production processes, and marketing strategies at Kopi Bang Marko. The linear programming model is then formulated based on the observed data, and the simplex method is applied to optimize the production and maximize profits. The optimal solution obtained through the simplex method indicates the ideal quantity of each coffee type to be sold per month, leading to maximum profit. This research contributes to the application of linear programming, specifically the simplex method, in optimizing sales and profits for a traditional Indonesian coffee SME. The findings offer practical insights for SMEs, especially those in the coffee business, on how to strategically plan production to maximize profits. The study may also have implications for policymakers in supporting and promoting the growth of SMEs. The study is limited to the specific case of Kopi Bang Marko in Tangerang Selatan and may not be directly applicable to other contexts without adjustments.